Dual-Band monopole Antenna For Energy Harvesting System - Zakaria, Z; Zainuddin, N. A; Abd Aziz, M. Z. A; Husain , M. N; Mutalib, M. A (2013)
A planar dual-band monopole antenna is presented for Global System for Mobile Communications (GSM) band applications, which also have the potential to be used for energy harvesting system. The proposed antenna comprises of a ground plane at the back of the FR4 substrate and three microstrip lines which are physically connected with each other at the top surface of the substrate. The monopole antenna achieves good return loss at resonance frequencies of 915 MHz and 1800 MHz with a bandwidth value of 124.2 MHz and 196.9 MHz respectively. The antenna gains of 1.97 dB and 3.05 dB are achieved at resonance frequencies of 900 MHz and 1800 MHz. Experimental results show good agreement with simulated performance. The output from the receiving antenna is also observed in order to analyze the relationship of the power level and the distance between transmitting and receiving antenna. This study is an early investigation in designing the RF energy harvesting system to support green technology and sustainable development particularly for Wireless Sensor Network (WSN) applications.